THE IMPORTANCE OF IMPLEMENTING MANAGEMENT IN ENTREPRENEURIAL ACTIVITIES - Novita Agistia Soraya; Erviany Dwiana Putri; Dewi Nurhasanah; Nendita Syalwa Nurfadillah; Dede Akhmad Sulaeman; Ujang Dedih Humaedih; Putra Adnyana Murthy; Chepiq Aziz (Management Studies and Business Journal (PRODUCTIVITY), 2026)
Management plays a crucial role in determining the success and sustainability of entrepreneurial activities, particularly in micro-enterprises with limited resources. Many businesses with promising market opportunities fail to grow optimally due to weak managerial implementation. This study aims to analyze the implementation of management functions in entrepreneurial activities at Fotocopy Istiqomah in West Bandung Regency. The study employed a qualitative approach with a descriptive method to comprehensively understand managerial practices based on actual field conditions. Research participants consisted of the business owner and employees selected purposively. Data were collected through semi-structured interviews, direct observation, and documentation studies, and analyzed using descriptive qualitative analysis techniques. The findings reveal that planning is the most dominant management function in maintaining business sustainability, although it is still carried out in a simple and undocumented manner. Organizing remains a major challenge, particularly in task allocation and work responsibilities. The leadership of the business owner plays a significant role in business implementation, while control and evaluation functions are still applied in a relatively simple manner. The study concludes that consistent implementation of management functions contributes significantly to the stability and sustainability of micro-enterprises.